Status prawny wysp naturalnych i sztucznych w nowym prawie morza - Symonides, Janusz (Wydział Prawa i Administracji UAM, 1984)
A problem of defining a notion of "island" and the related question of right to possess maritime territories was particilarly in focus at the III. Conference on the Law of Seas particularly in relation to the perspective of setting up exclusive economic zones. There is over half a million islands on the world ocean differing widely from each other in area, situation, mineral resources, fauna and flora. The right of inhabited islands to posess their own economic zones and continental shelf was not questioned in so far as a substantial part of states declared themselves in favor of limiting or excluding the right to posess economic zones or shelf by rocks or uninhabited small elevations. Compromised art, 121.3 provides that "Rocks which cannot sustain human habitation or economic life on their own shall have no exclusive economic zone or continental shelf". It can be inferred from that article that rocks retain their right to posess territorial sea and contiguous zone. Conceding a right to states to set up zone around uninhabited rocks to protect customs, fiscal immigration and sanitary interests can raise certain doubts. The Convention does not answer the question whether a state to which an island belongs can institute its contiguous zone in the exclusive economic zone of another subject. The very notion used in the wording of art. 121.3 is also not free of ambiguities. Is a notion of "rocks" to be understood verbally — it would not then contain coral-reefs, sandbanks as well as other smaller land formations. Formulations pertaining to inability to sustain human habitation or economic life can be a subject for discussion too. Making account for area sizes would simplify the whole problem. It has to be assumed though that differences in opinions in those questions will eventually find their solution on account of a procedure of peaceful settlement of disputes adopted in the convention. The problem gains a large practical importance in relation to the new possibilities of utilizing artificial islands and installations. The artificial islands can be divided into four categories: a) constructed on the. bottom and permanently tied to it, b) embeded on the bottom but movable, c) floating or rather bouyed and d) navigable. A coastal state has an exclusive right to erect artificial islands on its territorial sea in the exclusive zone or continental shelf. Right of other states to construct in economic zone installations and constructions for other than economic goals is controversial. A new solution adopted in the 1982 Convention is freedom to erect artificial islands on open seas. The said freedom is limited though by rights of coastal states in continental shelf on the one hand and on the other by provisions concerning bottom of seas and oceans recognized to be a common heritage of hummanity. In comparison to the 1953 Convention on Continental Shelf, the Convention on the Law of Seas made a step forward in defining a status of artificial islands, installations and constructions, Further specifying of numerous questions in the Convention as well as elimination of the existing loopholes to start with lack of definitions, questions of jurisdiction, to a detailed regulation of artificial islands status on the open sea.
The legal status of natural and artificial islands in the new law of seas